Chlorophyll-a Analysis in the Coastal Waters of Nusa Lembongan using Sentinel-2 Image Data - Sagung Putri Chandra Astiti; I Gusti Ngurah Kerta Arsana; I Putu Gustave Suryantara Pariartha (JRST (Jurnal Riset Sains dan Teknologi), 2025)
Nusa Lembongan is a potential area for seaweed cultivation and is the largest commodity producing the best seaweed on the island of Bali. This shows that the waters in Nusa Lembongan are included in fertile waters. One indicator in determining the level of fertility in a water area is by analyzing the chlorophyll-a value. One method for analyzing the chlorophyll-a value is using remote sensing methods. The image data used in this study were Sentinel-2A and Sentinel-2B level 1C image data. The calculation of chlorophyll-a analysis used the Case 2 Regional Coast Color (C2RCC) processor. The C2RCC processor used in the analysis is included in the Sentinel Application Platform (SNAP) application. The results of the analysis showed that the chlorophyll-a value in the dry season was higher than in the rainy season. The maximum value of chlorophyll-a analysis in the dry season was 40.92 mg/m3 while the maximum value of chlorophyll-a analysis in the rainy season was 40.89 mg/m3. The locations with the highest chlorophyll-a values ​​in the coastal waters of Nusa Lembongan are in the mangrove forest ecosystem in Jungutbatu Village, seaweed cultivation in Lembongan Village and coral reef ecosystem in Tanjung Ental.